Australian Legal Education – A Short History - Barker, David (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
This article examines the history and development of legal education in Australia by tracing the establishment of university law schools and other forms of legal education in the states and territories from the time of European settlement in 1788 until the present day. It considers the critical role played by legal education in shaping the culture of law and thus determining how well the legal system operates in practice. It argues that Australian legal education can satisfactorily meet the twin objectives of training individuals as legal practitioners, whilst providing a liberal education that facilitates the acquisition of knowledge and transferable legal skills.